A catalyst for preparing acrylonitrile by oxidation of propylene and its preparation method and application
By using composite oxides containing molybdenum, bismuth, and iron as active components and silica as the catalysts as support, combined with spray drying and calcining, the problems of high carbon yield and poor stability of the existing catalysts were solved, and acrylonitrile catalyst with low carbon yield and high stability were achieved.
Patent Information
- Application Number
- CN202111302982.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-11-04
AI Technical Summary
The existing acrylonitrile catalysts with high yield and poor stability are the problems of high carbon yield and poor stability.
The catalyst is prepared by spray drying and calcining by using composite oxides containing molybdenum, bismuth and iron as active components, combined with silica as support, and the performance of the catalyst is adjusted by controlling the crystal phase composition of the catalyst surface, especially the area ratio of peak A to peak B characterized by Raman spectroscopy.
The yield of two carbons is significantly reduced and the stability of the catalyst is improved, so that the reaction is carried out with high selectivity and stability, effectively controlling the problem of excessive yield of two carbons.
Smart Images

Figure CN116060031B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an ammoxidation catalyst, in particular to a catalyst for preparing acrylonitrile by ammoxidation of propylene, a preparation method thereof and application in the field of preparing acrylonitrile by ammoxidation of propylene. Background Art
[0002] Acrylonitrile is an important chemical raw material for fibers, rubbers and plastics, and is mainly used to produce acrylic fibers, ABS plastics, styrene plastics, acrylamide, etc. In industry, acrylonitrile is mainly produced using propylene as raw material and ammoxidation in a fluidized bed.
[0003] The technology of producing acrylonitrile by propylene ammoxidation has been successfully industrialized in acrylonitrile plants around the world. As one of the core technologies of this process, catalysts for producing acrylonitrile by propylene ammoxidation are constantly being researched and developed in order to produce catalysts with better comprehensive properties such as activity and selectivity.
[0004] At present, as a relatively mature ammonia oxidation catalyst, Mo-Bi catalyst has been widely used in industry. Mo-Bi catalyst can be prepared by spray drying, and the process is: metal precursor and carrier material are made into slurry, then spray dried, and then calcined. For example, CN1600423A discloses ammonia oxidation catalyst prepared by spray drying, and CN103769140A discloses acrylonitrile fluidized bed catalyst.
[0005] The process of propylene ammoxidation to acrylonitrile is a gas-solid surface reaction. The composition and ratio of the active phase on the catalyst surface are critical to the study of catalytic performance, but there is currently little research on the composition of the catalyst surface phase. Therefore, for propylene ammoxidation to acrylonitrile catalysts, developing Mo-Bi catalysts with both low two-carbon yields and high stability has been a goal that has been studied in this field. Summary of the invention
[0006] In order to solve the problem that the catalyst for preparing acrylonitrile by propylene ammoxidation has high carbon yield and poor stability in the prior art, the present invention provides a catalyst for preparing acrylonitrile by propylene ammoxidation and a preparation method and application thereof. The catalyst for preparing acrylonitrile by propylene ammoxidation has the characteristics of low carbon yield and high activity and stability.
[0007] The first aspect of the present invention provides a catalyst for preparing acrylonitrile by oxidation of propylene, the catalyst comprising an active component and a carrier, the active component being a composite oxide comprising molybdenum, bismuth and iron; the surface composition of the catalyst is characterized by Raman spectroscopy, wherein the surface composition of the catalyst is characterized by Raman spectroscopy at 784 cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak nearby is peak B, and the area ratio of peak A to peak B is 3.5-5.5.
[0008] Furthermore, based on the weight of the catalyst, the content of the active component in terms of oxide is 30%-90%, and the content of the carrier is 10%-70%.
[0009] Furthermore, the carrier is preferably a silica carrier.
[0010] Furthermore, the active component is a composite oxide comprising molybdenum, bismuth and iron. Furthermore, the active component is a composite oxide comprising molybdenum, bismuth, iron, rare earth elements, alkali metal elements and alkaline earth metal elements and other element Y.
[0011] Furthermore, the alkali metal element is selected from at least one of Li, Na, K, Rb and Cs; the alkaline earth metal element is selected from at least one of Be, Mg, Ca, Sr and Ba; the other element Y is selected from at least one of W, V, Zr, P, Nb, Ni, Co, Cr, Mn, Tl, Au, Ag, Pt, Ru, Rh, Pd, Ti, Sb, In, Sn and Te; and the rare earth element is selected from at least one of La, Ce, Pr, Nd and Sm.
[0012] Further, based on the weight of the catalyst,
[0013] The weight content of the Mo element calculated as MoO3 is 15%-55%, preferably 20%-45%,
[0014] The weight content of the Bi element calculated as Bi2O3 is 0.5%-3.5%, preferably 1.0%-3.5%,
[0015] The weight content of the Fe element calculated as Fe2O3 is 1%-12%, preferably 1.5%-11%.
[0016] The weight content of the rare earth element in the form of rare earth element oxide is 1.5%-8.5%, preferably 1.8%-5.0%.
[0017] The weight content of the alkali metal element calculated as oxide is 0.01%-0.60%, preferably 0.05%-0.55%,
[0018] The weight content of the alkaline earth metal in terms of oxide is 0.01%-4.0%, preferably 0.05%-3.5%.
[0019] The weight content of the other elements calculated as oxides is 0.01%-15%, preferably 0.05%-14%.
[0020] Furthermore, the active component in the catalyst is represented by the following general formula: a Fe b Yc R d T e Bi f Mo g O x , wherein Fe, Bi, Mo and O represent the elements iron, bismuth, molybdenum and oxygen respectively, X represents an alkali metal element, Y represents other elements, R represents an alkaline earth metal element, and T represents a rare earth element; a, b, c, d, e, f, g and x represent the atomic number of the corresponding element, the value of f / g is 0.008-0.25, the value of b / f is 2.0-11.0, the value of (e+a+d) / g is 0.05-0.4, the value of c / g is 0.01-1.0, and x is the number of oxygen atoms required to satisfy the total valence of other elements.
[0021] Furthermore, in the general formula of the active component, the value of f / g is preferably 0.01-0.20, including but not limited to: 0.02, 0.04, 0.05, 0.06, 0.07, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20 and the like.
[0022] Furthermore, in the general formula of the active component, the value of b / f is preferably 3.0-11.0, examples but not limited to: 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0 and the like.
[0023] Furthermore, in the general formula of the active component, the value of (e+a+d) / g is preferably 0.10-0.35, including but not limited to: 0.10, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35 and the like.
[0024] Furthermore, in the general formula of the active component, the value of c / g is preferably 0.02-0.90, including but not limited to: 0.02, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 045, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90 and the like.
[0025] Furthermore, in the catalyst, the area ratio of peak A to peak B is 3.5 to 5.5, including but not limited to: 3.5, 3.6, 3.8, 4.0, 4.2, 4.5, 4.8, 5.0, 5.2, 5.4, 5.5 and the like.
[0026] The second aspect of the present invention provides a method for preparing the above-mentioned catalyst for preparing acrylonitrile by propylene ammoxidation, comprising the following steps:
[0027] (1) mixing a carrier precursor and an active component precursor to obtain a first slurry, and heat-treating the first slurry to obtain a second slurry;
[0028] (2) spray drying the second slurry to obtain granules;
[0029] (3) calcining the particles to obtain the catalyst.
[0030] Furthermore, in step (1), the precursor of the rare earth element is first mixed with the carrier precursor, and then mixed with the precursors of other active components to obtain a first slurry, and the first slurry is heat-treated to obtain a second slurry;
[0031] Furthermore, the heat treatment temperature in step (1) is controlled at 100-150°C, wherein the heating rate of the heat treatment is controlled at 5-15°C / min, and the constant temperature is maintained for 5-30min.
[0032] Furthermore, the carrier precursor in step (1) is a silicon dioxide precursor, preferably a silica sol, wherein the solid content of the silica sol is 20 wt%-50 wt% in terms of silicon dioxide, and the average particle size is 10-35 nm.
[0033] Furthermore, the precursor of the active component described in step (1) includes a Mo precursor, a Bi precursor, a Fe precursor, a rare earth element precursor, an alkali metal element precursor, an alkaline earth metal element precursor, and a precursor of other elements Y.
[0034] Furthermore, in step (1), there is no particular limitation on the ratio between the active component precursors (Mo element precursor, Bi element precursor, Fe element precursor, rare earth element precursor, alkali metal element precursor, alkaline earth metal element precursor, other element Y precursor) and the carrier precursor or their respective amounts, as long as the content of each component in the final catalyst particles meets the requirements.
[0035] Furthermore, in step (1), there is no particular limitation on the Mo element precursor, which may be an oxide of Mo or any substance that can generate the oxide after calcination, such as oxides, hydroxides, inorganic acid salts, organic acid salts and ammonium salts of oxygen-containing acids (including hydrates of these compounds) of Mo, wherein water-soluble inorganic acid salts, water-soluble organic acid salts and ammonium salts of oxygen-containing acids of Mo are preferred, and ammonium salts of oxygen-containing acids of Mo are more preferred, such as (NH4)6Mo7O 24 or a hydrate thereof.
[0036] Further, in step (1), there is no particular limitation on the precursors of Bi element, Fe element, rare earth element, alkali metal element, alkaline earth metal element and other element Y, and they may be oxides of the corresponding elements or any substance that can generate the oxides after calcination, such as oxides, hydroxides, inorganic acid salts and organic acid salts (including hydrates of these compounds) of the corresponding elements, preferably water-soluble inorganic acid salts and water-soluble organic acid salts, more preferably halides, alcohol salts, nitrates and acetates, especially nitrates. These precursors may be used alone or in combination in any proportion.
[0037] Furthermore, the spray drying method in step (2) is not particularly limited and can be conventionally selected by a person skilled in the art. The spray drying conditions include: the drying heat source is air, the drying temperature is 250-350°C, preferably 300-350°C, the drying time is 0.1-2.0h, preferably 0.2-1.0h, and the average diameter of the spray droplets is 20-200μm, preferably 40-180μm.
[0038] Furthermore, the calcination in step (3) is carried out in two stages, the first stage calcination conditions are: calcination temperature of 200-300°C, calcination time of 0.5-5h, and heating rate of 1-5°C / min; the second stage calcination conditions are: calcination temperature of 500-750°C, calcination time of 0.5-5h, and heating rate of 8-20°C / min. The calcination is carried out in an oxygen-containing atmosphere. In the oxygen-containing atmosphere, the volume content of oxygen is generally greater than 0% and less than 100%, preferably greater than 0% and less than 50%, relative to the total volume of the oxygen-containing atmosphere.
[0039] The third aspect of the present invention provides a method for preparing acrylonitrile by ammoxidation of propylene, comprising: in the presence of the above catalyst or the catalyst prepared by the above preparation method, ammoxidation of propylene to produce acrylonitrile, the reaction conditions are: the molar ratio of propylene: ammonia: air (in terms of O2) is 1: 1.1-1.35: 1.8-2.5, the reaction temperature is 420-440°C, the reaction pressure is 0.03-0.14 MPa in gauge pressure, and the weight hourly space velocity is 0.04-0.10 h -1 .
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The inventors have found that the crystal phase composition of the catalyst surface for the ammoxidation of propylene to acrylonitrile has a significant influence on the catalyst performance. The inventors have further found that the catalyst surface is characterized by Raman at 784 cm -1 The characteristic peaks near and at 830cm -1When the area ratio of the characteristic peaks nearby is 3.5-5.5, the two-carbon yield can be significantly reduced and the catalyst stability can be improved. The possible reason is that the stable ratio of the crystal phase on the catalyst surface is beneficial to the catalyst having sufficient active sites for adsorption and reaction of the reaction gas during the reaction, so that the reaction can be carried out stably and moderately with high selectivity, effectively controlling the problem of excessively high two-carbon yield.
[0042] (2) The present invention can significantly reduce the two-carbon yield and improve the catalyst stability by controlling the heat treatment and calcination process during the catalyst preparation process. The possible reason is that the stable ratio of the crystal phase on the catalyst surface is conducive to the sufficient active sites of the catalyst for adsorption and reaction of the reaction gas during the reaction process, so that the reaction can be carried out stably and moderately with high selectivity, effectively controlling the problem of excessively high two-carbon yield.
[0043] (3) When the catalyst of the present invention is used for the ammoxidation of propylene to produce acrylonitrile, it has a lower two-carbon yield and can significantly improve the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a Raman spectrum of the catalyst surface obtained in Example 1;
[0045] Figure 2 is the Raman spectrum of the catalyst surface obtained by comparative agent 1;
[0046] Figure 3 This is a diagram of the stability performance of the catalyst obtained in Example 1. DETAILED DESCRIPTION
[0047] In the present invention, Raman spectroscopy is tested using a 325nm wavelength laser as the excitation light source and a LabRAMAramis spectrometer from Horiba JobinYvon. All samples are placed on a clean glass slide for testing. -1 The peak near (denoted as peak A) and the peak at 830 cm -1 The ratio of the area occupied by the nearby peak (referred to as peak B) is S A / S B .
[0048] In the present invention, the two carbons refer to CO and CO2, and the yield of the two carbons (%) = (the total moles of carbon monoxide and carbon dioxide generated by the reaction / the moles of propylene feed are calculated in terms of carbon moles) × 100%.
[0049] In the present invention, the definitions of propylene conversion and acrylonitrile selectivity are as follows:
[0050] Propylene conversion rate (%) = (moles of propylene consumed in the reaction / moles of propylene fed) × 100%,
[0051] Acrylonitrile selectivity (%) = (the number of moles of acrylonitrile produced by the reaction / the number of moles of acrylonitrile consumed by the reaction) × 100%.
[0052] The present invention will be further described below by way of examples.
[0053] [Example 1]
[0054] 154.4 g of Pr(NO3)3·6H2O was dissolved in water, and 2750 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 3.64 g of KOH, 139.1 g of Bi(NO3)3·5H2O, 526.6 g of Ni(NO3)2·6H2O, 798.8 g of Fe(NO3)3·9H2O, and 137.9 g of Mg(NO3)2·6H2O were added into water and dissolved to obtain solution I. 826.9 g of (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 120°C at a rate of 10°C / min, and the temperature is maintained at a constant temperature for 10 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 5°C / min to 300°C, stay for 30 minutes, and then raised to 550°C at 20°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0055] 50%K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 1.0 Bi 0.8 Mo 13 O x +50%SiO2.
[0056] The Raman characterization images of the above catalysts are shown in Figure 1 ,Depend on Figure 1 Clearly visible at 784cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B is 4.05.
[0057] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After running for 300 hours, the reaction results are as follows: propylene conversion is 99.5%, and CO+CO2 yield is 6.5%.
[0058] [Example 2]
[0059] 124.4 g of Nd(NO3)3·6H2O was dissolved in water, and 3300 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 2.91 g of KOH, 69.4 g of Bi(NO3)3·5H2O, 416.6 g of Co(NO3)2·6H2O, 638 g of Fe(NO3)3·9H2O, 110.1 g of Mg(NO3)2·6H2O, and 101.4 g of Mn(NO3)2 were added into water and dissolved to obtain solution I. 660.4 g of (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 120°C at a rate of 15°C / min, and the temperature is maintained at a constant temperature for 20 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 5°C / min to 300°C, stay for 30 minutes, and then raised to 550°C at 20°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0060] 40%K 0.15 Fe 5.46 Co 5.0 Mn 1.0 Mg 1.5 Nd 1.0 Bi 0.5 Mo 13 O x +60%SiO2.
[0061] The Raman characterization of the above catalyst is similar to Figure 1 , clearly visible at 784cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S BIt is 3.72.
[0062] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 300 hours of operation, the reaction results were as follows: propylene conversion was 99.1%, and CO+CO2 yield was 6.8%.
[0063] [Example 3]
[0064] 168.7 g of La(NO3)3·6H2O was dissolved in water, and 2200 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 9.62 g of RbNO3, 4.15 g of CrO3, 105.4 g of Bi(NO3)3·5H2O, 632.6 g of Co(NO3)2·6H2O, 968.8 g of Fe(NO3)3·9H2O, and 154 g of Ca(NO3)2·6H2O were added into water and dissolved to obtain solution I. 1002.8 g of (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 100°C at a rate of 5°C / min, and the temperature is maintained at a constant temperature for 10 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 5°C / min to 300°C, stay for 30 minutes, and then raised to 550°C at 20°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0065] 60% Rb 0.15 Fe 5.46 Co 5.0 Cr 0.1 Ca 1.5 La 1.0 Bi 0.5 Mo 13 O x +40%SiO2.
[0066] The Raman characterization of the above catalyst is similar to Figure 1 , clearly visible at 784cm -1The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B is 4.55.
[0067] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 300 hours of operation, the reaction results were as follows: propylene conversion was 98.9%, and CO+CO2 yield was 6.4%.
[0068] [Example 4]
[0069] 74 g of Sm(NO3)3·6H2O was dissolved in water, and 2200 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 9.39 g of RbNO3, 4.21 g of CrO3, 103 g of Bi(NO3)3·5H2O, 623.6 g of Ni(NO3)2·6H2O, 946 g of Fe(NO3)3·9H2O, and 134.8 g of Sr(NO3)2 were added into water and dissolved to obtain solution I. 979.2 g of (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 120°C at a rate of 10°C / min, and the temperature is maintained at a constant temperature for 20 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 5°C / min to 300°C, stay for 30 minutes, and then raised to 550°C at 20°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0070] 60% Rb 0.15 Fe 5.46 Ni 5.0 Cr 0.1 Sr 1.5 Sm 1.0 Bi 0.5 Mo 13 O x +40%SiO2.
[0071] The Raman characterization of the above catalyst is similar to Figure 1 , clearly visible at 784cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B It is 3.78.
[0072] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 100 hours of operation, the reaction results were as follows: propylene conversion was 99.1%, and CO+CO2 yield was 6.7%.
[0073] [Example 5]
[0074] 73.7 g of Sm(NO3)3·6H2O was dissolved in water, and 2200 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 9.36 g of RbNO3, 4.27 g of CrO3, 102.6 g of Bi(NO3)3·5H2O, 621.3 g of Ni(NO3)2·6H2O, 942.6 g of Fe(NO3)3·9H2O, 134.3 g of Sr(NO3)2, and 2.4 g of H3PO4 were added into water and dissolved to obtain solution I. 975.7 g of (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 120°C at a rate of 10°C / min, and the temperature is maintained at a constant temperature for 25 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 5°C / min to 300°C, stay for 30 minutes, and then raised to 550°C at 20°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0075] 60% Rb 0.15 P 0.05 Fe 5.46 Ni 5.0 Cr 0.1 Sr1.5 Sm 1.0 Bi 0.5 Mo 13 O x +40%SiO2
[0076] The Raman characterization of the above catalyst is similar to Figure 1 , clearly visible at 784cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A :S B The area ratio is 4.22.
[0077] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After running for 300 hours, the reaction results were as follows: propylene conversion was 98.9%, and CO+CO2 yield was 7.0%.
[0078] [Example 6]
[0079] 222.2 g of Pr(NO3)3·6H2O was dissolved in water, and 2200 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 6.34 g of RbNO3, 4.34 g of CrO3, 2.91 g of KOH, 104.3 g of Bi(NO3)3·5H2O, 631.6 g of Ni(NO3)2·6H2O, 958.2 g of Fe(NO3)3·9H2O, and 152.3 g of Ca(NO3)2·6H2O were added into water and dissolved to obtain solution I. 991.8 g of (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 120°C at a rate of 10°C / min, and the temperature is maintained at a constant temperature for 10 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 5°C / min to 300°C, stay for 30 minutes, and then raised to 550°C at 20°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0080] 60% Rb 0.10 K 0.1 Fe 5.46 Ni 5.0 Ca 1.5 Cr 0.1 Pr 1.2 Bi 0.5 Mo 13 O x +40%SiO2.
[0081] The Raman characterization of the above catalyst is similar to Figure 1 , clearly visible at 784cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B It is 5.18.
[0082] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 300 hours of operation, the reaction results were as follows: propylene conversion was 99.2%, and CO+CO2 yield was 7.2%.
[0083] [Example 7]
[0084] 273.4 g of Pr(NO3)3·6H2O was dissolved in water, and 2200 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 6.24 g of RbNO3, 4.28 g of CrO3, 2.87 g of KOH, 102.7 g of Bi(NO3)3·5H2O, 621.7 g of Ni(NO3)2·6H2O, 943.1 g of Fe(NO3)3·9H2O, and 149.9 g of Ca(NO3)2·6H2O were added into water and dissolved to obtain solution I. 976.3 g of (NH4)6Mo7O 24·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 120°C at a rate of 10°C / min, and the temperature is maintained at a constant temperature for 10 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 3°C / min to 300°C, and it stays for 30 minutes, and then it is increased to 550°C at 15°C / min and stayed for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0085] 60% Rb 0.10 K 0.1 Fe 5.46 Ni 5.0 Ca 1.5 Cr 0.1 Pr 1.5 Bi 0.5 Mo 13 O x +40%SiO2
[0086] The Raman characterization of the above catalyst is similar to Figure 1 , clearly visible at 784cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B It is 5.05.
[0087] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 300 hours of operation, the reaction results were as follows: propylene conversion was 99.8%, and CO+CO2 yield was 7.0%.
[0088] [Comparative Example 1]
[0089] 154.4 g of Pr(NO3)3·6H2O was dissolved in water, and 2750 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 3.64 g of KOH, 139.1 g of Bi(NO3)3·5H2O, 526.6 g of Ni(NO3)2·6H2O, 798.8 g of Fe(NO3)3·9H2O, and 137.9 g of Mg(NO3)2·6H2O were added into water and dissolved to obtain solution I. 826.9 g of (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 120°C at a rate of 10°C / min, and the temperature is maintained at a constant temperature for 10 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 20°C / min to 550°C, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0090] 50%K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 1.0 Bi 0.8 Mo 13 O x +50%SiO2.
[0091] The Raman characterization images of the above catalysts are shown in Figure 2 ,Depend on Figure 2 Clearly visible at 784cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B It is 2.30.
[0092] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 100 hours of operation, the reaction results were as follows: propylene conversion was 99.9%, and CO+CO2 yield was 8.6%.
[0093] [Comparative Example 2]
[0094] 154.4 g of Pr(NO3)3·6H2O was dissolved in water, and 2750 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 3.64 g of KOH, 139.1 g of Bi(NO3)3·5H2O, 526.6 g of Ni(NO3)2·6H2O, 798.8 g of Fe(NO3)3·9H2O, and 137.9 g of Mg(NO3)2·6H2O were added into water and dissolved to obtain solution I. 826.9 g of (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 120°C at a rate of 10°C / min, and the temperature is maintained at a constant temperature for 10 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 10°C / min to 300°C, stay for 30 minutes, and then raised to 550°C at 5°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0095] 50%K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 1.0 Bi 0.8 Mo 13 O x +50%SiO2.
[0096] The Raman characterization of the above catalyst clearly shows that the -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B is 2.01.
[0097] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 100 hours of operation, the reaction results were as follows: propylene conversion was 99.8%, and CO+CO2 yield was 8.7%.
[0098] [Comparative Example 3]
[0099] 154.4 g of Pr(NO3)3·6H2O was dissolved in water, and 2750 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 3.64 g of KOH, 139.1 g of Bi(NO3)3·5H2O, 526.6 g of Ni(NO3)2·6H2O, 798.8 g of Fe(NO3)3·9H2O, and 137.9 g of Mg(NO3)2·6H2O were added into water and dissolved to obtain solution I. 826.9 g of (NH4)6Mo7O 24 ·4H2O was dissolved in water to obtain solution I. 836.6 g (NH4)6Mo7O 24 ·4H2O is dissolved in water, added to the above slurry I, stirred for 10 minutes, and then slowly added to solution I, stirred to form a slurry. The slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, the average diameter of the spray droplets is 100μm, and particles are obtained. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 5°C / min to 300°C, stay for 30 minutes, and then rise to 550°C at 20°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0100] 50%K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 1.0 Bi 0.8 Mo 13 O x +50%SiO2.
[0101] The Raman characterization of the above catalyst clearly shows that the -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B It is 1.58.
[0102] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 100 hours of operation, the reaction results were as follows: propylene conversion was 98.7%, and CO+CO2 yield was 8.2%.
[0103] [Comparative Example 4]
[0104] 154.4 g of Pr(NO3)3·6H2O was dissolved in water, and 2750 g of silica sol with a weight concentration of 40% was added at 30°C. After stirring for 30 min, slurry I was formed. 3.64 g of KOH, 139.1 g of Bi(NO3)3·5H2O, 526.6 g of Ni(NO3)2·6H2O, 798.8 g of Fe(NO3)3·9H2O, and 137.9 g of Mg(NO3)2·6H2O were added into water and dissolved to obtain solution I. 826.9 g of (NH4)6Mo7O 24 ·4H2O was dissolved in water to obtain solution I. 836.6 g (NH4)6Mo7O 24 ·4H2O is dissolved in water, and the above slurry I is added, stirred for 10 minutes, and solution I is slowly added. After stirring, a first slurry is formed. The first slurry is heated to 100°C at a rate of 20°C / min, and the temperature is maintained at a constant temperature for 10 minutes to obtain a second slurry. The second slurry is formed into microspheres in a spray dryer, the drying temperature is 300°C, the drying time is 0.5h, and the average diameter of the spray droplets is 100μm to obtain particles. Finally, it is calcined in an air atmosphere, and the calcination heating rate is controlled at 5°C / min to 300°C, stay for 30 minutes, and then raised to 550°C at 20°C / min, and stay for 45 minutes. The composition of the catalyst obtained according to the above steps is expressed as follows:
[0105] 50%K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 1.0 Bi 0.8 Mo 13 O x +50%SiO2
[0106] The Raman characterization of the above catalyst clearly shows that the -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak near is the B peak, where S A / S B It is 2.89.
[0107] The evaluation conditions for the reaction of the above catalyst for producing acrylonitrile by propylene ammoxidation are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After 100 hours of operation, the reaction results were as follows: propylene conversion was 98.8%, and CO+CO2 yield was 8.9%.
[0108] Table 1 Composition and evaluation results of catalyst particles obtained in various examples and comparative examples
[0109]
[0110]
[0111] The embodiments of the present invention are only detailed descriptions of the technical solutions of the present invention, but the present invention is not limited to the above embodiments, that is, the present invention can be implemented without relying on the steps described in the above embodiments. In summary, any improvements made by those skilled in the art to the present invention, including replacement of the raw materials and additives described in the present invention, selection of specific implementation methods, etc., all belong to the protection scope and disclosure scope of the present invention.
Claims
1. A catalyst for preparing acrylonitrile by ammoxidation of propylene, characterized in that: The catalyst comprises an active component and a carrier, wherein the active component is a composite oxide comprising molybdenum, bismuth and iron; the surface composition of the catalyst is characterized by Raman spectroscopy, wherein the surface composition of the catalyst is characterized by Raman spectroscopy at 784 cm -1 The characteristic peaks near the A peak and the peak at 830cm -1 The characteristic peak nearby is peak B, and the area ratio of peak A to peak B is 3.5-5.
5.
2. The catalyst according to claim 1, characterized in that Based on the weight of the catalyst, the content of the active component in terms of oxide is 30%-90%, and the content of the carrier is 10%-70%.
3. The catalyst according to claim 1, characterized in that The carrier is a silicon dioxide carrier; and / or the active component includes a composite oxide of molybdenum, bismuth, iron, rare earth elements, alkali metal elements and alkaline earth metal elements and other elements Y.
4. The catalyst according to claim 3, characterized in that The alkali metal element is selected from at least one of Li, Na, K, Rb and Cs; and / or the alkaline earth metal element is selected from at least one of Be, Mg, Ca, Sr and Ba; and / or the other element Y is selected from at least one of W, V, Zr, P, Nb, Ni, Co, Cr, Mn, Tl, Au, Ag, Pt, Ru, Rh, Pd, Ti, Sb, In, Sn and Te; and / or the rare earth element is selected from at least one of La, Ce, Pr, Nd and Sm.
5. The catalyst according to claim 2, 3 or 4, characterized in that Based on the weight of the catalyst, The weight content of the Mo element calculated as MoO3 is 15%-55%, The weight content of the Bi element calculated as Bi2O3 is 0.5%-3.5%, The weight content of the Fe element calculated as Fe2O3 is 1%-12%, The weight content of the rare earth element in the form of rare earth element oxide is 1.5%-8.5%. The weight content of the alkali metal element in terms of oxide is 0.01%-0.60%, The weight content of the alkaline earth metal in terms of oxide is 0.01%-4.0%, The weight content of the other elements calculated as oxides is 0.01%-15%.
6. The catalyst according to claim 2, 3 or 4, characterized in that Based on the weight of the catalyst, The weight content of the Mo element calculated as MoO3 is 20%-45%, The weight content of the Bi element calculated as Bi2O3 is 1.0%-3.5%, The weight content of the Fe element calculated as Fe2O3 is 1.5%-11%. The weight content of the rare earth element in the form of rare earth element oxide is 1.8%-5.0%. The weight content of the alkali metal element in terms of oxide is 0.05%-0.55%, The weight content of the alkaline earth metal in terms of oxide is 0.05% to 3.5%. The weight content of the other elements calculated as oxides is 0.05%-14%.
7. The catalyst according to claim 5, characterized in that The active component in the catalyst is represented by the following general formula: a Fe b Y c R d T e Bi f Mo g O x , wherein X represents an alkali metal element, Y represents other elements, R represents an alkaline earth metal element, and T represents a rare earth element; the value of f / g is 0.008-0.25, the value of b / f is 2.0-11.0, the value of (e+a+d) / g is 0.05-0.4, the value of c / g is 0.01-1.0, and x is the number of oxygen atoms required to satisfy the total valence of other elements.
8. The catalyst according to claim 5, characterized in that The active component in the catalyst is represented by the following general formula: a Fe b Y c R d T e Bi f Mo g O x , wherein X represents an alkali metal element, Y represents other elements, R represents an alkaline earth metal element, and T represents a rare earth element; the value of f / g is 0.01-0.20, the value of b / f is 3.0-11.0, the value of (e+a+d) / g is 0.10-0.35, the value of c / g is 0.02-0.9, and x is the number of oxygen atoms required to satisfy the total valence of other elements.
9. The method for preparing the catalyst for preparing acrylonitrile by propylene ammoxidation according to any one of claims 1 to 8, comprising the following steps: (1) mixing a carrier precursor and an active component precursor to obtain a first slurry, and heat-treating the first slurry to obtain a second slurry; (2) spray drying the second slurry to obtain granules; (3) calcining the particles to obtain the catalyst.
10. The method according to claim 9, characterized in that The heat treatment temperature in step (1) is controlled at 100-150°C, wherein the heating rate of the heat treatment is controlled at 5-15°C / min, and the constant temperature is maintained for 5-30min.
11. The method according to claim 9, characterized in that The carrier precursor described in step (1) is a silicon dioxide precursor.
12. The method according to claim 9, characterized in that The carrier precursor described in step (1) is silica sol, the solid content of the silica sol is 20wt%-50wt% in terms of silicon dioxide, and the average particle size is 10-35nm.
13. The method according to claim 9, characterized in that The spray drying conditions in step (2) include: the drying heat source is air, the drying temperature is 250-350° C., the drying time is 0.1-2.0 h, and the average diameter of the spray droplets is 20-200 μm.
14. The method according to claim 9, characterized in that The spray drying conditions in step (2) include: the drying heat source is air, the drying temperature is 300-350° C., the drying time is 0.2-1.0 h, and the average diameter of the spray droplets is 40-180 μm.
15. The method according to claim 9, characterized in that The calcination in step (3) is carried out in two stages. The first stage calcination conditions are: calcination temperature of 200-300°C, calcination time of 0.5-5h, and heating rate of 1-5°C / min; the second stage calcination conditions are: calcination temperature of 500-750°C, calcination time of 0.5-5h, and heating rate of 8-20°C / min; the calcination is carried out in an oxygen-containing atmosphere.
16. A method for preparing acrylonitrile by ammoxidation of propylene, comprising: In the presence of the catalyst described in any one of claims 1 to 8 or the catalyst prepared by the preparation method described in any one of claims 9 to 15, propylene undergoes an ammoxidation reaction to obtain acrylonitrile.
17. The method according to claim 16, characterized in that The reaction conditions are: the molar ratio of propylene: ammonia: air in terms of O2 is 1: 1.1-1.35: 1.8-2.5, the reaction temperature is 420-440°C, the reaction pressure is 0.03-0.14 MPa in terms of gauge pressure, and the weight hourly space velocity is 0.04-0.10 h -1 .
Citation Information
Patent Citations
Acrylonitrile fluid catalyst and preparation method thereof
CN103769140A
Method for preparing fluid bed catalyst in use for ammoxidation reaction of olefin
CN1600423A
A process for manufacturing acrylic acid, acrylonitrile and 1,4-butanediol from 1,3-propanediol
CN105705647A
Ammoxidation catalyst particles as well as preparation method and application thereof
CN111744493A